Analysis of genetic variability among citrus (Citrus spp) genotypes using morphological traits - MARBOH, E S; SINGH, A K; DUBEY, A K; PRAKASH, J (The Indian Journal of Agricultural Sciences, 2015)
Fifty citrus (Citrus spp) genotypes comprising cultivars, strains and hybrids were characterized by using morphological characters in this study. Twenty quantitative characters from leaves, flowers and fruits were evaluated and morphological data from fifty accessions were submitted to one-way ANOVA, principal component and cluster analysis. The matrix of average dissimilarity between genotypes was estimated using Euclidean distance. Significant variation in quantitative characteristics among genotypes was observed. The average distance ranged from 0.09 - 3.77. The clustering pattern clearly differentiates the genotypes into separate clusters based on their dissimilarity values. The first 3 principal components explained 58.72% of variation and identified seeds/fruit, juice content, pH, TSS, TSS:TA and petal size as important traits that can be used to differentiate genotypes. Among all genotypes, small fruited mandarins were highly diverse while sweet orange and grapefruit genotypes presented the lowest diversity. The high diversity observed within the genotypes points to ample possibilities of obtaining desirable trait combinations in specific cultivars.